ECONOMIC RECESSION’S MITIGATION: INTERPRETATION OF QS. YUSUF [12]: 43-48 WITH SEMIOTIC APPROACH - Muhammad Saiful Khair; Desi Erawati; Nor Faridatunnisa (Aqlam: Journal of Islam and Plurality, 2023)
Abstract:  At the end of 2022, the world community was shocked by the issue of global economic recession. This threat is considered very worrying because it can cause the collapse of a country if there are no mitigation measures for this issue. Therefore, a reinterpretation of QS. Yusuf [12]: 43-48 using Roland Barthes' semiotic approach as an analytical was needed so that the Indonesian people could apply the strategies used by the Prophet Yusuf in dealing with the famine in Egypt in facing the threat of economic recession. The results show that improving the quality of human resources, especially in managing natural resources, is the primary key so that people can have a productive spirit and can create new jobs for others. In addition, implementing good regulations in all sectors of life and building good synergy between all elements of society are supporting factors in efforts to prevent the phenomenon of recession.Keyword: Recession Mitigation, QS. Yusuf [12]: 43-48, SemioticsAbstrak: Di penghujung tahun 2022, masyarakat dunia dikejutkan dengan isu resesi ekonomi global. Ancaman ini dinilai sangat mengkhawatirkan karena dapat menyebabkan keruntuhan suatu negara jika tidak ada langkah mitigasi atas isu ini. Oleh karena itu, muncullah penafsiran ulang terhadap QS. Yusuf [12]: 43-48 dengan menggunakan pendekatan semiotika Roland Barthes sebagai pisau analisis diperlukan agar masyarakat Indonesia dapat menerapkan strategi yang digunakan oleh Nabi Yusuf dalam menghadapi bencana kelaparan di Mesir dalam menghadapi ancaman resesi ekonomi. Hasil penelitian menunjukkan bahwa peningkatan kualitas sumber daya manusia terutama dalam mengelola sumber daya alam menjadi kunci utama agar masyarakat dapat memiliki jiwa yang produktif dan dapat menciptakan lapangan pekerjaan baru bagi orang lain. Selain itu, penerapan regulasi yang baik di semua sektor kehidupan dan membangun sinergi yang baik antara semua elemen masyarakat menjadi faktor pendukung dalam upaya pencegahan fenomena resesi.Kata Kunci: Mitigasi Resesi, QS. Yusuf [12]: 43-48, Semiotika